2012
DOI: 10.1002/arch.21044
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF A CALMODULIN‐BINDING SITE WITHIN THE DOMAIN I OF BACILLUS THURINGIENSISCry3Aa TOXIN

Abstract: Bacillus thuringiensis Cry3Aa toxin is a coleopteran specific toxin highly active against Colorado Potato Beetle (CPB).We have recently shown thatCry3Aa toxin is proteolytically cleaved by CPBmidgut membrane associated metalloproteases and that this cleavage is inhibited by ADAMmetalloprotease inhibitors. In the present study, we investigated whether the Cry3Aa toxin is a calmodulin (CaM) binding protein, as it is the case of several different ADAMshedding substrates. In pull‐down assays using agarose beads co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…On L. decemlineata , it has been shown that ADAM metalloprotease serves as receptor for Cry3Aa toxin [68]. Cry3Aa toxin specifically binds to calmodulin (CalM) in a calcium-independent manner [69] and also to the toxin-binding fragments of cadherin [70]. We have taken in consideration these three genes in our analyses and using scientific literature, we built a catalog of those genes known to be involved in resistance to Bt, including several transcripts recently isolated from Diabrotica virgifera showing responses to the Bt toxin Cry3Bb1 [71].…”
Section: Resultsmentioning
confidence: 99%
“…On L. decemlineata , it has been shown that ADAM metalloprotease serves as receptor for Cry3Aa toxin [68]. Cry3Aa toxin specifically binds to calmodulin (CalM) in a calcium-independent manner [69] and also to the toxin-binding fragments of cadherin [70]. We have taken in consideration these three genes in our analyses and using scientific literature, we built a catalog of those genes known to be involved in resistance to Bt, including several transcripts recently isolated from Diabrotica virgifera showing responses to the Bt toxin Cry3Bb1 [71].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the ADAM metalloprotease serves as a receptor for the Cry3Aa toxin in L. decemlineata (Ochoa-Campuzano et al 2007). Additionally, the Cry3Aa toxin also binds to calmodulin in a calcium-independent manner (Ochoa-Campuzano et al 2012) and to cadherin fragments (Park et al 2009). By using a pyrosequencing strategy on the 454-FLX platform of Roche, Kumar et al identified 621 contigs involved in insecticide resistance; of these three contigs belonged to metalloprotease ADAM, 10 to cadherin, and 98 to calmodulin, among others (Kumar et al 2014).…”
Section: Transcriptome As Tool To Identify New Proteins Involved In Tmentioning
confidence: 99%
“…The mode of action of Cry proteins from B. thuringiensis has been extensively studied, especially for lepidopteran-active Cry proteins (Bravo et al., 2007, Vachon et al., 2012; Adang et al., 2014), whereas much less is known for coleopteran-active Cry proteins (Hernández-Martínez et al., 2014, Ochoa-Campuzano et al., 2012, Rausell et al., 2004, Rausell et al., 2007, Slaney et al., 1992). The proposed model starts after the ingestion of the crystals by susceptible insect larvae, followed by crystal solubilization and protease activation in the midgut environment.…”
mentioning
confidence: 99%